PENGARUH VARIASI (JARAK PENEKANAN)TERHADAP KEKUATAN SAMBUNGAN LAS GESEK (FRICTION WELDING) PADA BAJA KARBON S45C - Muhammad Rizqi fadilah; Rodika Rodika; Fajar Aswin (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Friction welding is a welding technique that melts metal. Jointing of metals by utilizing the heat generated by friction between metal surfaces in which variations in the pressure distance are determined. The purpose of this study is to determine the strength of the welded joint after the welding process by using variations in the pressure distance of 3mm, 4mm, and 5mm. The material used in this research is carbon steel S45C shaft. Studies have shown that welding at the deepest compression distance produces a very strong welded joint, the greater the stress during the welding process, the stronger the joint in the welding. Welding with compression distances of 4mm and 5mm. and the impact price is higher compared to the 3mm pressing distance.